The Effects of sodium bicarbonate Ringer's solution on acute kidney injury and the clinical outcomes after liver transplantation: A randomized controlled trial - Hao Wu; Hao Wu; Gaige Meng; Chunlong Zuo; Jiang Wang; Shiyun Jin; Lijian Chen; Ye Zhang (Frontiers Media S.A., 2022)
Background: Acute kidney injury is the most common complication after liver transplantation. Sodium bicarbonate Ringer's solution is a new type of crystalloid solution that has been recently used in the clinical setting. Whether sodium bicarbonate Ringer's solution reduces the occurrence of postoperative AKI and improves the clinical outcomes of liver transplantation patients is not clear.Objective: To compare the effects of sodium bicarbonate Ringer's solution versus normal saline on acute kidney injury and clinical outcomes following classic orthotopic liver transplantation.Methods: Sixty-four participants were randomly assigned to the sodium bicarbonate Ringers (BRS) group or the normal saline (NS) group. The primary outcomes were the incidence and severity of acute kidney injury after liver transplantation. The secondary outcomes included the rate of renal replacement therapy, length of mechanical ventilation, stay in the ICU, stay in the hospital after surgery and 30-day mortality. Other outcomes included the concentration of sodium, chloride, bicarbonate, anion gap, lactate concentration and changes in chloride preoperatively and postoperatively.Result: Sixty-two patients completed the trial and were analyzed, with 31 patients in each group. There was a significantly lower rate of postoperative acute kidney injury in the BRS group (14/31, 45.2%) than in the NS group (24/31, 77.4%), with a relative risk of 0.58 (95% CI, 0.38-0.90; p = 0.009). The severity of AKI in the BRS group was lower than that in the NS group (Z = -2.932, p = 0.003). There was no significant difference observed in the secondary outcomes. For other outcomes, the concentration of preoperative sodium was lower than postoperative sodium in the NS group (137.2 vs. 140.4, p = 0.009). The concentration of preoperative chloride was lower than that of postoperative chloride in the NS group (102.9 vs. 106.2, p < 0.001). The change in the concentration of chloride in the BRS group was lower than that in the NS group (1.6 vs. 4.7, p = 0.006).Conclusion: Sodium bicarbonate Ringer's solution reduced the incidence and severity of acute kidney injury after classic orthotopic liver transplantation.